1988
DOI: 10.1161/01.str.19.11.1359
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia is a stress response in acute stroke.

Abstract: To explore further the relation between admission glucose concentration and outcome in stroke, we measured glucose, fructosamine, and glycosylated hemoglobin concentrations on admission in 216 patients seen within 24 hours after the onset of their first stroke. Fructosamine concentration reflects the degree of glycemia in the preceding 4-6 weeks and glycosylated hemoglobin concentration reflects that in the preceding 3 months. Based on clinical, computed tomographic, and necropsy findings, strokes were classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 29 publications
0
33
0
1
Order By: Relevance
“…18 However, although both serum ferritin and glycemia are elevated during stress, the weak correlation with serum cortisol and the fact that ferritin was selected as the predictive independent variable in the logistic regression analysis suggest that high ferritin levels may have a direct neurotoxic effect in ischemic acute stroke.…”
Section: Resultsmentioning
confidence: 99%
“…18 However, although both serum ferritin and glycemia are elevated during stress, the weak correlation with serum cortisol and the fact that ferritin was selected as the predictive independent variable in the logistic regression analysis suggest that high ferritin levels may have a direct neurotoxic effect in ischemic acute stroke.…”
Section: Resultsmentioning
confidence: 99%
“…6 In any given stroke population the prevalence of diabetes is approximately 8% to 20%, with a further 6% to 42% having evidence of previously unrecognized diabetes before the acute event. 2,[7][8][9][10][11] Such estimates are, however, complicated by the high prevalence of poststroke hyperglycemia; in one series of acute stroke patients it was estimated that up to 68% had poststroke hyperglycemia, defined by a plasma glucose concentration Ͼ6.0 mmol/L. 2 It is possible that poststroke hyperglycemia is primarily a stress response in relation to stroke size and severity 12 : however, poststroke hyperglycemia is prevalent across all clinical subtypes and severities of stroke and is not restricted to those most severely affected.…”
Section: Diabetes or Poststroke Hyperglycemia?mentioning
confidence: 99%
“…16,17 However, initial human studies reported no association between hyperglycemia and stroke outcome, suggesting that the former represented a stress response to the latter. 18 Several reports since then have shown that hyperglycemia, especially immediately after symptom onset, is indeed related to worse outcome in patients with AIS. 9,10,19 -21 This association is evident in patients with nonlacunar strokes but not in those with lacunar ones.…”
Section: Effect Of Hyperglycemia On Ais Outcomementioning
confidence: 99%